Surgical decision-making for individuals with differences of sex development: Stakeholders’ views - Weidler, Erica M.; Gardner, Melissa; Suorsa-Johnson, Kristina I.; Schafer-Kalkhoff, Tara; Rutter, Meilan M.; Sandberg, David E.; van Leeuwen, Kathleen (Frontiers in Urology, 2023)
Introduction: Advocacy and human rights organizations have called for a moratorium on elective surgical procedures until the patient is able to fully participate in the decision-making process. Due to the controversial nature surrounding surgery in differences of sex development (DSD) care, we aimed to assess the factors that teens and adults with DSD, parents, healthcare providers and other allied professionals consider pertinent to complex surgical decisions in DSD. Methods: Stakeholders (n=110) in DSD care participated in semi-structured interviews exploring features and potential determinants of successful healthcare outcomes. Audio-recordings were transcribed, coded, and analyzed using qualitative data software. Codes for “Process of Decision-Making” and “Successful Outcome–Surgery/Appearance/Function” were further searched using keywords “surgery,” “procedure,” and “timing.” Results: Several themes were identified: 1) The nature or type of the decision being made; 2) Who should be involved in the decision-making process; 3) Timing of conversations about surgery; 4) Barriers to decision-making surrounding surgery; 5) The elements of surgical decision-making; and 6) The optimal approach to surgical decision-making. Many stakeholders believed children and adolescents with DSD should be involved in the process as developmentally appropriate. Conclusion: DSD include a wide range of diagnoses, some of which may require urogenital reconstruction to relieve obstruction, achieve continence, and/or address other anatomical differences whether cosmetic or functional. Adolescents and adults with DSD desired autonomy and to be part of the decision-making process. Parents were divided in their opinion of who should be involved in making elective surgical decisions: the child or parents as proxy medical decision-makers. Providers and other professionals stressed the importance of process and education around surgical decisions. Ongoing research examines how decision-makers evaluate tradeoffs associated with decision options.